Biomechanics-based analysis of technical characteristics in skeleton start and specific physical training strategies - Hao, Lei; Kong, Qingtao (Frontiers in Physiology, 2026)
PurposeThis study employed kinematic and kinetic testing to analyze the sport-specific parameters of the skeleton start, thereby elucidating its technical characteristics and establishing an empirical basis for training.MethodsSpatiotemporal parameters were captured using a 3D motion system, while ground reaction forces, impulses, and plantar pressure distribution were collected via a Ki-Sprint force platform and custom pressure sensors. Statistical analysis employed descriptive statistics, two-way ANOVA to evaluate factor effects, and appropriate parametric or non-parametric tests for group comparisons.ResultsAthletes’ average starting distance was 18.45 ± 2.09 m, achieved in 12.20 ± 1.11 steps, with no gender difference. Starting speed (male: 6.97 ± 0.42 m/s, female: 6.25 ± 0.58 m/s) and acceleration range (male: 3.31–6.26 m/s2, female: 2.14–5.96 m/s2) differed significantly by gender. Step length differed between push-off (1.60 ± 0.14 m) and follow-up steps (2.09 ± 0.18 m), and between inner (2.60 ± 0.14 m, 0.44 ± 0.03 s) and outer steps (2.64 ± 0.13 m, 0.45 ± 0.03 s) in both length and duration. Take-off (2.71 ± 0.50 m) and preceding step (2.81 ± 0.58 m) lengths did not differ. The maximum horizontal force was 826.99 ± 217.18 N and average horizontal impulse was 264.43 ± 67.64 N·s, neither correlating with front-rear foot spacing. Average plantar pressure was higher during run-up (1.77 ± 0.76 kg/cm2) than take-off (1.19 ± 0.59 kg/cm2).ConclusionThe skeleton start is characterized by periodic speed-power movements akin to a hybrid of sprint acceleration and diving. Training should integrate regular sprints, specialized push simulations, and downhill sprinting to improve acceleration and maximal speed. Core stability, lower-limb maximal strength, and multi-joint power training should be implemented with consideration for gender-specific adaptations.